Field Performance of Transgenic Sugarcane Lines Resistant to Sugarcane Mosaic Virus - Yao, Wei; Ruan, Miaohong; Qin, Lifang; Yang, Chuanyu; Chen, Rukai; Chen, Baoshan; Zhang, Muqing (Frontiers in Plant Science, 2017)
Sugarcane mosaic disease is mainly caused by the sugarcane mosaic virus (SCMV), which can significantly reduce stalk yield and sucrose content of sugarcane in the field. Coat protein mediated protection (CPMP) is an effective strategy to improve virus resistance. A 2-year field study was conducted to compare five independent transgenic sugarcane lines carrying the SCMV-CP gene (i.e., B2, B36, B38, B48, and B51) with the wild-type parental clone Badila (WT). Agronomic performance, resistance to SCMV infection, and transgene stability were evaluated and compared with the wild-type parental clone Badila (WT) at four experimental locations in China across two successive seasons, i.e., plant cane (PC) and 1st ratoon cane (1R). All transgenic lines derived from Badila had significantly greater tons of cane per hectare (TCH) and tons of sucrose per hectare (TSH) as well as lower SCMV disease incidence than those from Badila in the PC and 1R crops. The transgenic line B48 was highly resistant to SCMV with less than 3% incidence of infection. The recovery phenotype of transgenic line B36 was infected soon after virus inoculation, but the subsequent leaves showed no symptoms of infection. Most control plants developed symptoms that persisted and spread throughout the plant with more than 50% incidence. B48 recorded an average of 102.72 t/ha, which was 67.2% more than that for Badila. The expression of the transgene was stable over many generations with vegetative propagation. These results show that SCMV-resistant transgenic lines derived from Badila can provide resistant germplasm for sugarcane breeding and can also be used to study virus resistance mechanisms. This is the first report on the development and field performance of transgenic sugarcane plants that are resistant to SCMV infection in China.